1994
DOI: 10.1093/jaoac/77.5.1083
|View full text |Cite
|
Sign up to set email alerts
|

Particle Concentration Fluorescence Immunoassay for Determination of Tylosin in Premix, Feeds, and Liquid Feed Supplement: Comparison with Tiirbidimetric Assay

Abstract: A rapid, competitive particle concentration fluorescence immunoassay (PCFIA) for the determination of tylosin (Tylan) concentrations in extracts of pre-mix, feeds (cattle, chicken, and swine), and liquid feed supplement is described. Tylosin-β-phyco-erythrin conjugate, tylosin standard or diluted sample extracts, and rabbit anti-tylosin antibody are incubated for 15 min in PCFIA plates. Rabbit anti-tylosin antibody is then captured, during a 15 min incubation, with goat anti-rabbit antibody that is attached to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Based on these results, we speculated that the four antibodies mainly bind A ring and C ring, because they showed negligible cross-reactivity (CRs B1%) to the MACs that do not contain the two rings (erythromycin, spiramycin and avermectin, data not shown). The CRs of these antibodies to the four analytes were better than those of the previously reported antibodies (Beier et al, 2005;Jackman et al, 1997;Peng et al, 2012;Silverlight et al, 1999;Wicker et al, 1994;Yao and Mahoney, 1989).…”
Section: Antibody Performancecontrasting
confidence: 52%
See 1 more Smart Citation
“…Based on these results, we speculated that the four antibodies mainly bind A ring and C ring, because they showed negligible cross-reactivity (CRs B1%) to the MACs that do not contain the two rings (erythromycin, spiramycin and avermectin, data not shown). The CRs of these antibodies to the four analytes were better than those of the previously reported antibodies (Beier et al, 2005;Jackman et al, 1997;Peng et al, 2012;Silverlight et al, 1999;Wicker et al, 1994;Yao and Mahoney, 1989).…”
Section: Antibody Performancecontrasting
confidence: 52%
“…The antibody showed crossreactivity (CR) to the 12-, 14-and 16-membered macrolides that contain amino sugar moieties. Wicker et al (1994) prepared a polyclonal antibody against TYL that cross-reacted with TMC. Jackman, Spencer, Silverlight, Marsh, and Bellerby (1997) produced a polyclonal antibody against DMC and Silverlight, Brown, and Jackman (1999) showed the anti-DMC antibody exhibited high CR (96%) with TYL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous polyclonal antibodies produced to a conjugate through the C20 aldehyde group of tylosin ( 15) had about equal crossreactivity with tylosin as they did with tilmicosin (16). Polyclonal antibodies produced to tylosin also cross-reacted to tilmicosin (17), and polyclonal antibodies produced to 23-deoxy-23-amino-O-mycaminosyltylonolide cross-reacted with various sized macrolides that possessed an amino sugar (18). In an attempt to produce antibodies specific for tilmicosin that did not bind tylosin, we developed this specificity by synthesizing the hapten 23-demycinosyl-23-deoxy-23-(3-aminoprop-1-yl)aminotilmicosin (Figure 2) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Jackman et al (15) reported preparation of polyclonal antibodies against desmycosin, conjugated through the C20 aldehyde group; however, such polyclonal antibodies also had 96% cross-reactivity with tylosin (16). Wicker et al (17) reported the use of polyclonal antibodies to tylosin in a fluorescence immunoassay for detecting tylosin in premix and feeds. The antibodies produced to tylosin also cross-reacted with tilmicosin.…”
Section: Introductionmentioning
confidence: 99%